Survey Report on Sending Data Securely using IoT over Cloud - Singh, Om Prakash; C. S, Ranjith; R., Karthik; Reddy, Sandeep; Soni, Rashmi (International Journal of Recent Technology and Applied Science (IJORTAS), 2020)
The Internet of Things (IoT) is the network of physical objects, computers, cars, houses, and other things embedded with electronics, software, sensors, and network connectivity, allowing these objects to collect and exchange data. In the new technology market, IoT innovations is the next major step, but with the big difference that it brings about massive changes in business usability. A flare in the number of connected devices as well as placed locations is anticipated over the next few years and the functions that they will perform. Due to recent developments in networking and sensor technology, the Internet of Things (IoT) has grown rapidly. It seems very difficult to link that object together through the internet, but within a time frame, the internet of things will change our lives dramatically.